CITRUS YELLOW MOSAIC: A TRANSMISSIBLE VIRUS OF CITRUS SPIECES IN INDIA - GADDAM SUSMILA APARNA,; VENKATA SUBBAIAH KOTAKADI,; , D. V. R. SAIGOPAL,; M. N. REDDY, (The Bioscan, 2012)
The yellow mosaic disease of citrus is one of the important diseases causing heavy losses in citrus industry. In the present study, an attempt has been made to analyze certain studies on host range and transmission in citrus yellow mosaic virus infecting Rangapur lime, sweet orange and acid lime. The virus disease of citrus was recognized by mosaic symptoms were noticed in sweet orange, Rangapur lime and acid lime plants. Systemically infected Rangapur lime, sweet orange and acid lime leaves showing characteristic yellow mosaic were collected from AICRP on Tropical Fruits (Citrus), Tirupati. During the present investigations major efforts were made on characterization of CYMV and following information have been generated. The virus under study has a narrow host range. Mechanically sap transmissible from rangpur lime to rangpur lime, sweet orange and acid lime among the citrus hosts and to Canna indica, maize and sorghum in non-citrus hosts. Pure cultures of the virus were developed by sap transmission and there have been used in experiments. The virus culture was maintained on citrus plants. Studies on graft transmission indicated that T-budding (65.56%) and back patch (61.7%) were the best in per cent transmission than leaf patch (42.5%) grafting. The CYMV transmission from sweet orange to sweet orange and Rangapur lime; Rangapur lime to sweet orange and Rangapur lime; and acid lime to acid lime was found better. The transmission of CYMV was very low when it was from acid lime to sweet orange and rangpur lime and vice versa. The citrus mosaic virus was also transmitted by mealy bug, Planococcus citri after 48h acquisition feeding and 4 days inoculation feeding.